The Effect of Working Capital Turnover and Receivables Turnover on Profitability in Automotive Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Febriani, Shiva Dwi; Mulyani, Sri; Nuridah, Siti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to examine the effect of working capital turnover and accounts receivable turnover on profitability. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the automotive sub-sector for the 2019-2023 period. The sampling technique used in this study is a purposive sampling technique consisting of 9 companies that meet the criteria. The analysis technique used in this study is multiple linear regression analysis with the hypothesis test used is a partial test, simultaneous test and coefficient of determination. The results of this study indicate that partially working capital turnover does not affect profitability. In addition, accounts receivable turnover in this study also has no effect on profitability. Simultaneously working capital turnover and accounts receivable turnover do not affect profitability, this is indicated by the results of the f test which shows the calculated f value is smaller than the f table. This indicates an imbalance between sales and production. However, the results of the determination coefficient test (R2) show that Working Capital Turnover and Receivables Turnover affect Profitability or Return on Investment by 17.9%. While the remaining 82.1% (100% - 17.9%) is influenced by other variables not examined in this study. The results of this study provide practical implications for company management, especially the automotive sub-sector, in order to improve the effectiveness of working capital and receivables management to achieve a higher level of profitability and design a more efficient long-term financial management strategy.